Development of Animated Media-based Discovery Learning to Improve Scientific Literacy Content for Senior High School Students in Human Circulatory System Material - Andika Widiyana; Risya Pramana Situmorang; Marisa Christina Tapilouw (Pendidikan Kimia Unimus, 2021)
This study aims to: 1) develop animation media-based Discovery Learning on the circulatory system material, 2) determine the feasibility of the media-based Discovery Learning on the circulatory system material, and 3) examine the effectiveness of the media in increasing the dimensions of scientific literacy on content dimension in class XI IPA SMA. This type of research is research and development using the ADDIE model as steps for product development. The test instrument is used to measure the content dimension of scientific literacy content. The subjects of this study were high school students of class XI Science with a total of 30 students at Yasiha Gubug by taking purposive sampling. The media is validated by the validator of media experts, material experts, and Biology teachers as a user. The results of media expert' validation concluded that media was valid with a score of 83.19% and material expert judgment obtained a score of 82.77% included a valid category. Test the effectiveness of the product using paired sample t-test with the acquisition of 0,000 <0.05 means that the animation media-based Discovery Learning is significant to the content dimension of scientific literacy. Based on the N-gain test, animation media-based Discovery Learning can also increase the content dimension of scientific literacy of score 52% with enough categories.